2013
DOI: 10.1016/j.nbd.2013.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of neural stem/progenitor cell proliferation during experimental Herpes Simplex encephalitis is mediated by differential FGF-2 expression in the adult brain

Abstract: Neural stem cells (NSCs) respond to inflammatory cues induced during brain injury and are thought to be involved in recovery from brain damage. Little is known about NSC response during brain infections. The present study evaluated NSC proliferation during Herpes Simplex Virus-1 brain infection. Total numbers of nestin(+) NSCs increased significantly in infected brains at 6 d post infection (p.i.). However, by 15 d p.i. the nestin(+) population decreased significantly below levels observed in uninfected brains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…Based on this observation, we hypothesized NPCs may be vulnerable to HSV-1 either by direct cytopathic effect or alternatively, by altering the population of differentiated progeny cells. Consistent with this hypothesis, a recent study reported intranasal infection with HSV-1 led to an initial rise then subsequent decrease in transplanted nestin 1 NSCs in the brain of mice (Rotschafer et al, 2013). In fact, we found ocular infection with HSV-1 led to a FIGURE 11: Neutralization of IL-6 blocks microglia-induced preservation of neuroblasts.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Based on this observation, we hypothesized NPCs may be vulnerable to HSV-1 either by direct cytopathic effect or alternatively, by altering the population of differentiated progeny cells. Consistent with this hypothesis, a recent study reported intranasal infection with HSV-1 led to an initial rise then subsequent decrease in transplanted nestin 1 NSCs in the brain of mice (Rotschafer et al, 2013). In fact, we found ocular infection with HSV-1 led to a FIGURE 11: Neutralization of IL-6 blocks microglia-induced preservation of neuroblasts.…”
Section: Discussionsupporting
confidence: 88%
“…I n vitro models suggested MG and MG-CM could direct NPC migration and facilitate the differentiation of NPC toward a neuronal phenotype (Aarum et al, 2003; Walton et al, 2006). In contrast, the analysis of in vivo models using HSV-1 have led some to suggest MG activation along with leukocyte infiltration contribute to the neuropathology of HSE (Marques et al, 2008) including a detrimental outcome to NPC maintenance (Rotschafer et al, 2013). Our data support a beneficial role of MG in maintaining the neuronal phenotype of NPC cultures challenged with HSV-1.…”
Section: Discussionmentioning
confidence: 99%
“…As the SVZ is proximal to the lateral ventricles and NPCs are infected during HSE (8), it is tempting to speculate the neurologic deficits observed in the majority of surviving HSE patients are due to the simmering HSV lytic infection that alters environmental cues of NPC differentiation within the EP as a result of the host anergic T cell response to infection. To this end, experimental evidence suggests latent HSV-1 infection does alter NPC proliferation as a result of FGF2 deficits (90) resulting in behavioral changes in mice (10). …”
Section: Discussionmentioning
confidence: 99%
“…This same study also found under conditions that drive NPC differentiation, there is a predilection in blocking neuroblast development without any obvious effect on astrocyte or oligodendrocyte differentiation. This phenotype was recapitulated in vivo where NPC numbers were reduced during the peak of viral encephalitis following both ocular and intranasal infection (Chucair-Elliott, Conrady, 2014, Rotschafer et al, 2013). Since experimental animal models have demonstrated viral tropism towards cortical tissue surrounding the lateral ventricles and hippocampus, these findings correlate with the involvement of similar tissue during human encephalitis.…”
Section: Acute Infection Of Herpes Simplex Virus-1 In the Nervous mentioning
confidence: 92%